Structural analysis of unusual alkaloids isolated from Narcissus pseudonarcissus cv. Carlton - Křoustková, Jana; Ritomská, Aneta; Al Mamun, Abdullah; Hulcová, Daniela; Opletal, Lubomír; Kuneš, Jiří; Cahlíková, Lucie; Bucar, Franz (Phytochemistry, 2022)
Narciindole A, the first representative of Amaryllidaceae alkaloids with an indol-3-ylmethanone framework, was isolated from bulbs of Narcissus pseudonarcissus (L.) cv. Carlton, together with carltonine D and carltonine E, which share the same unusual structural motif as dimeric carltonine C (reported in 2020), exhibiting atropisomerism. Unambiguous structure elucidations have been achieved by NMR spectroscopy, HRMS, and comparison with literature data of related alkaloids. Furthermore, the chirality of known alkaloids with a galanthindole biaryl core was revised using optical rotation. Last, but not least, a biosynthetic pathway for dimeric carltonine-type alkaloids was proposed. Unfortunately, in terms of biological activity, the isolated alkaloids showed only moderate inhibition of human acetylcholinesterase and/or butyrylcholinesterase.
Keywords: Carltonines; Amaryllidaceae; Narcissus pseudonarcissus (L.) cv. Carlton; Atropisomerism; Alkaloids; Specific rotation revised; Structure elucidation; Alzheimer's disease